CLOZAPINE-INDUCED DIABETIC KETOACIDOSIS: A CASE REPORT - Alex, Soumya Mary; Menon, Vidya P; B, Sabarish; P, Umadevi; T s, Dipu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The objective of this study was to report a case of a person with psychiatric illness treated with clozapine presented with diabetic ketoacidosis (DKA). A clinical monitoring was done on a 38-year-old Indian man affected by schizoaffective disorder, bipolar type presented with DKA after 3 months of clozapine therapy (250 mg/day). After treatment of DKA and discontinuation of clozapine, the patient improved symptomatically, his blood sugar levels normalized and insulin requirements also decreased. This report thus highlights that clinicians should be vigilant about the potential risk of new-onset diabetes and DKA in patients taking clozapine and utilize appropriate clinical and laboratory monitoring early in the course of treatment to prevent serious adverse effects.